استراتيجيات القراءة لدى طلبة اللغة العربية فى جامعة فترا الماليزية ومدى تأثيرها على مستوى استيعابهم القرائي /‏ - Nik Farhan binti Mustapha
The study aims at discovering the reading strategies among students majoring in Arabic Language and the related impacts on their comprehension. A sample of fourteen male and female students was selected from Universiti Putra Malaysia. A set of data on the strategies applied in reading an academic text in Arabic were gathered through a think aloud process, observations and retrospective interviews. Accordingly, the data were analyzed based on the six Oxford groups of strategies (1990); namely - cognitive, memory, compensation, metacognitive, affective and social. In addition, the analysis was also complemented and strengthened by a number of Islamic elements used by the students in their reading process. With regard to their reading levels, the relevant data were collected through a process of 'immediate written recall', and thereafter, they were subjected to Johnson's recall protocol scoring system (1970) - the 'pausal acceptability units'. The results revealed that above all else the students preferred the strategy of asking questions to seek clarification when reading the Arabic text. They also used the cognitive strategies a great deal as reflected by the thought process on translation method, which stood out prominently. Besides, the associating and elaborating strategy was also much in use. Most of the students in the sample relied on the strategies of solving the problems on the lexical level. They sorely lacked the ability to broaden the application of the strategies and continually failed to differentiate the difference between the least and the most effective strategies for understanding the Arabic text. The researcher concluded that the understanding levels neither relied on the types nor the number of strategies employed, rather on how best they were employed individually. It was also duly noted that the strategies were interspersed with a number of Islamic elements such as the recitation of prayers, the utterance of bismillah and alhamdulillah, as these elements are strongly and closely related to the six Oxford groups of strategies.